2019
DOI: 10.1029/2019ja026928
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Trends in the Low‐Latitude Middle Atmosphere Temperature and Winds: Observations and WACCM‐X Model Simulations

Abstract: In recent years, the middle atmosphere has evoked great scientific interest as long‐term changes can be clearly captured owing to the large perturbation amplitudes at these altitudes. In the present study, more than 25 years of the data are used to investigate the long‐term trends in the middle atmosphere by suitably combining the observations from different techniques (Rocketsonde, High‐Resolution Doppler Imager (HRDI)/Upper Atmosphere Research Satellite (UARS), Halogen Occultation Experiment (HALOE)/UARS, So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…In addition, observational studies have assessed the variability with the measurements available (e.g., Lee et al, 2010; Sridharan et al, 2009, 2010; Venkat Ratnam et al, 2013, 2019); see the reviews by Beig et al (2003) and Laštovička (2017). Both simulations and observational analyses are important to improve our understanding of the atmospheric response to the various external and anthropogenic changes that have occurred and are expected to continue.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, observational studies have assessed the variability with the measurements available (e.g., Lee et al, 2010; Sridharan et al, 2009, 2010; Venkat Ratnam et al, 2013, 2019); see the reviews by Beig et al (2003) and Laštovička (2017). Both simulations and observational analyses are important to improve our understanding of the atmospheric response to the various external and anthropogenic changes that have occurred and are expected to continue.…”
Section: Introductionmentioning
confidence: 99%
“…Han et al () suggest that the residual circulation is changing driven by climate change, resulting in changing transport of trace gases in the stratosphere. Venkat Ratnam et al () found a large decreasing trend (~5 m/s per decade) in the eastward winds between 70 and 80 km in Indian region, using multi‐instrumental data. So far, the reports on local wind or wave trends are often contradictory (Jacobi et al, ; Liu et al, ).…”
Section: Reviews Of Recent Workmentioning
confidence: 99%
“…Venkat Ratnam et al (2019) carefully merged data on the middle atmosphere over India obtained by various measuring techniques (rockets, High-Resolution Doppler Imager (HRDI)/ Upper Atmosphere Research Satellite (UARS), (HALOE)/UARS, SABER/TIMED and Mesosphere-Stratosphere-Troposphere (MST) radars) over more than 25 years. The observational analysis was accompanied by WACCM-X model simulations.…”
Section: Mesosphere and Lower Thermospherementioning
confidence: 99%